2016
DOI: 10.1080/0886022x.2016.1227918
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect ofL-glutamine against diabetes-induced nephropathy in experimental animal: Role of KIM-1, NGAL, TGF-β1, and collagen-1

Abstract: Diabetic nephropathy is a serious microvascular complication and one of the main causes of endstage renal disease. L-Glutamine (LG) is naturally occurring amino acids with antidiabetic and antioxidant potential. The aim of present investigation was to evaluate the potential of LG against streptozotocin (STZ)-induced diabetic nephropathy (DN) in laboratory rats. DN was induced in male Wistar rats (200-220 g) by intraperitoneal administration of STZ (55 mg/kg). Animals were treated orally with either distilled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 86 publications
(77 reference statements)
3
15
0
Order By: Relevance
“…In this study, reduction of the renal tubular injury markers, KIM-1 and NGAL by linagliptin might be due to the inhibition of high glucose-induced renal tubular damage and fibrosis. These findings are in agreement with a previous study that indicated that sitagliptin, a DPP-4 inhibitor, normalized blood glucose levels accompanied with a significant inhibition in KIM-1 and NGAL mRNA expression in STZ-induced DN in rats [36]. In context, KIM-1 was significantly reduced by the GLP-1 agonist, exendin-4, in rats subjected to renal ischemia/ reperfusion injury [37].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study, reduction of the renal tubular injury markers, KIM-1 and NGAL by linagliptin might be due to the inhibition of high glucose-induced renal tubular damage and fibrosis. These findings are in agreement with a previous study that indicated that sitagliptin, a DPP-4 inhibitor, normalized blood glucose levels accompanied with a significant inhibition in KIM-1 and NGAL mRNA expression in STZ-induced DN in rats [36]. In context, KIM-1 was significantly reduced by the GLP-1 agonist, exendin-4, in rats subjected to renal ischemia/ reperfusion injury [37].…”
Section: Discussionsupporting
confidence: 82%
“…To the authors' knowledge, this is the first study that evaluates the effect of a DPP-4 inhibitor on renal vanin-1 in experimental DN. The antioxidant properties attributed to DPP-4 inhibitors were depicted in experimental diabetic models [36,52] and T2D patients [53].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, HbA1c showed important negative correlations with ACR and BMD. This result reinforces the results of previous studies that poor glycaemic control leads to increased AGE production that is responsible for abnormally activating the protein kinase C pathway; stimulating the synthesis of extracellular matrix proteins, such as fibronectin, laminin and collagen; and inducing glomerular damage . In addition, hyperglycaemia leads to a delay in bone mineral acquisition in children and adolescents with T1D due to the long‐term disease duration promoting the increased formation of AGEs in the bone collagen matrix, directly affecting the bone structure and stimulating the apoptosis of osteoblastic cells that leads to reduced bone strength and contributes to fractures due to bone fragility .…”
Section: Discussionsupporting
confidence: 89%
“…Compared with imaging techniques, serum biomarkers are easier and cheaper for patients (8,9). In the past two decades, neutrophil gelatinase-associated lipocalin (NGAL) has received widespread clinical attention as a biomarker for kidney damage, cardiovascular damage and cancer (10)(11)(12). NGAL, also known as lipocalin-2 (lcn2), is a 24 kDa glycoprotein in humans encoded by the lcn2 gene located at position 3P11 of chromosome 9.…”
Section: Introductionmentioning
confidence: 99%